Problem-solving Approach and Its Impact on Creative Thinking Ability of Prospective Mathematics Teachers - Al Jupri; Hidayat, Asep Syarif (Mathematics Education Journal, 2022)
This study aims to investigate the implementation of a problem-solving approach and its corresponding impact on the creative thinking ability of prospective mathematics teachers. A qualitative case study approach was used in this study in the form of observations of learning and teaching processes for geometry topics through the use of a problem-solving approach and of a written test involving 20 prospective mathematics teachers, in one of the state universities in Bandung, Indonesia. The results showed that the implemented problem-solving approach influenced prospective mathematics teachers’ creative thinking in solving problems. The use of different strategies showed prospective teachers’ creative thinking ability in problem-solving processes. The effect of the problem-solving approach on prospective mathematics teachers can be investigated further to obtain a more comprehensive understanding of creative thinking ability. DOI : https://doi.org/10.22342/jpm.16.3.17820.257-268